Broadband low-frequency diffuse sound transmission loss of multilayer composite plate-type metamaterials - Boxin Chang; Shuaixing Wang; Gaoge Liang; Quanxing Liu; Yong Xiao (Composites Part C: Open Access)
Low-frequency sound insulation is one of the most challenging problems in the field of noise control engineering because of the classical mass law. Recent studies have shown that acoustic metamaterials can achieve a sound transmission loss (STL) higher than the mass law at specific low frequencies. However, it is still difficult to realize superior STL that can deeply break the mass law over a broadband low-frequency range, especially under the excitation of diffuse field sound. To challenge this problem, we suggest a multilayer composite plate-type metamaterial (MCPM) consisting of two single-layer metamaterial plates and a sandwiched layer of porous material. The metamaterial plates are simply constructed by a thin plate attached with periodic strip masses. We present an in-depth theoretical analysis and experimental verification of the STL performance of the MCPM. The results indicate that with proper design, the MCPM can achieve an excellent diffuse STL over an ultra-broadband low-frequency range, while avoiding the significant reduction of immediately following high-frequency STL. Owing to its simple construction yet superior low-frequency diffuse sound insulation performance, the MCPM can find promising applications in noise control engineering.